Determinants of Impulsive Buying Behaviour in Social Commerce: A Stimulus–Organism–Response Framework Perspective - ME Moses; A Nkoyi; Prof F van der Walt (The Retail and Marketing Review, 2021)
Impulsive buying has been an area of interest in the marketing discipline for years. Impulsive buying behaviour has both positive and negative outcomes, in the sense that retailers usually exploit consumers’ impulsiveness to increase their profits. However, these unplanned purchase decisions are problematic for consumers. Impulsive buying behaviour can disrupt consumers’ financial stability and can have negative emotional effects on them. This type of buying behaviour also hinders consumers’ ability to save, which may affect individuals’ financial position. While impulsive buying behaviour has been extensively studied, not much research has been conducted on how it manifests in the context of social commerce in South Africa. As a result, the aim of this study is to identify and model elements that are important in understanding impulsive buying in social commerce. A quantitative method and a survey design were employed, and 297 responses were collected from South African consumers. The structural relationships in the proposed research model were tested using partial least squares structural equation modeling. The study found out that consumers’ urge to buy impulsively is influenced by hedonic value, and impulsive buying behaviour is influenced by urge to buy impulsively. The findings of this study add to the body of knowledge by broadening our knowledge of how impulsive buying behaviour manifests in social commerce, especially in the setting of South Africa.